Enhanced Surface-Enhanced Raman Scattering (SERS) Sensitivity by the Self-Assembly of Silver Nanoparticles (Ag NPs) Laminated on Polydimethylsiloxane (PDMS). (12th December 2019) - Zhu, Lele; Dai, Hui; Zhang, Shuyun; Hu, Die; Zhou, Qun; Zou, Mingqiang; Adkins, Jason; Zheng, Junwei
Abstract: Herein, a transparent and reproducible substrate, fabricated using polydimethylsiloxane (PDMS) laminated with self-assembled Ag nanoparticles (Ag NPs), was employed as a universal surface-enhanced Raman scattering (SERS) substrate for the detection of targets with various matrices. The Ag NPs were assembled in a two-dimensional manner via a self-assembly technique. Due to the electrostatic interaction between the Ag NPs, the reproducibility of the assembly was ensured by the fixed density of the assembled Ag NPs at saturated assembly states. The assembled pattern and plasmon resonance of the Ag NPs were well preserved during the molding and curing of PDMS. As a result, the Ag NP laminated PDMS film exhibited a SERS effect to the adsorbed p -aminothiophenol comparable to that of the assembled Ag NPs on a glass slide. Extra SERS enhancement was achieved by construction of a Ag (PDMS)/molecule/Ag (glass) configuration due to the electromagnetic coupling between the Ag NPs. The Raman scattering of 4-mercaptobenzoic acid and benzotriazole modified on the surfaces of a smooth Au electrode and copper foil, respectively, was detected with the aid of the Ag NP-laminated PDMS film. Furthermore, malachite green dispersed in a KBr solid matrix was quantitatively determined with a detection limit of 0.5 μg/g. It is suggested that the SERS enhancement and consequential SERS detection sensitivity of the target molecules may be further maximized by adjusting the distance between the target molecules and the Ag NPs laminated on the PDMS film.